ANALISIS PROFIL SENYAWA PREKURSOR PENYUSUN GAHARU PADA KULTUR PUCUK AQUILARIA MALACCENSIS YANG DIELISITASI DENGAN ISOLAT FUNGI ENDOFIT - Paramitha Sowantara, Tania
Agarwood is a distinct aromatic compound that is formed by the defense mechanism of plants due to stress or pressure. One of the plant species that can produce Agarwood is Aquilaria malaccensis. The main components of Agarwood are sesquiterpenes and 2-(2-Phenethyl)chromones. Various studies have been conducted to accelerate the process of Agarwood formation, one of which is by using biological elicitors such as fungi. In this study, elicitation will be conducted on the shoots of Aquilaria malaccensis using fungal isolates to produce Agarwood components. The elicitation process will be carried out for 7 days, using liquid Murashige & Skoog (MS) media with carbon sources in the form of sucrose and soluble starch with variations of 4 g/L (control, without using fungal isolates), 2 g/L, and 6 g/L. The elicited A. malaccensis shoots will then be extracted using the maceration method with methanol solvent for 24 hours. Analysis of the compound profile will be conducted using Gas Chromatography Mass Spectrometry (GC-MS). In this study, a growth curve will also be created to determine the age of the fungal inoculum to be used in the elicitation process. Based on the results of the study, the fungal isolate used as an elicitor is suspected to come from the genus Lasiodiplodia sp. with a growth rate of 0.0089 g/day. Based on the GC-MS analysis, fatty acid compounds such as hexadecanoic acid, octadecadienoic acid, and nonahexacontanoic acid were found, as well as aromatic compounds such as lavandulyl acetate and neophytadiene, and phenolic compounds such as phenol, monophenol, 2-Isopropenyl-5-methyl-4-hexenyl acetate, and hexahydro-4,7-dimethyl. However, phenolic compounds were only found in samples elicited with fungal inoculum. The presence of sesquiterpenes and 2-(2-Phenethyl)chromones was not found in this study.